Nilai Islam melalui Tradisi Mbarak - Adah, Umi Musya; Zahro, Indah Rohmatuz (Proceedings of Annual Conference for Muslim Scholars, 2024)
Indonesia is a very large country and has a lot of cultural diversity in various regions. In terms of tradition, Islam also upholds traditions that develop among society. Not least, the traditions and customs that the majority of Muslims in Indonesia adhere to are in accordance with Islamic teachings. Like the tradition of mbarak during the Eid al-Fitr holiday carried out by the Tutul Tegalsari Ambulu Jember community. This tradition has been preserved for generations by the Tutul Tegalsari Ambulu Jember community as an effort to maintain and strengthen ties of friendship as well as harmony and tolerance. This article discusses the traditional practice of mbarak in Tutul. This article explains the Islamic values of hablum minannas contained in the Mbarak tradition which is the local wisdom of the Tutul community, the benefits and objectives contained in the Mbarak tradition, as well as efforts to maintain and preserve it. This mbarak tradition has been carried out for generations and has very high relevance in efforts to maintain harmony and tolerance in the Tutul community. By implementing the Islamic values of hablum minannas, it turns out that society can become more unified, harmonious, harmonious, peaceful, tolerant, and able to make society far from conflict and strife.